2015
DOI: 10.1371/journal.pone.0126495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Depth, Seasonal Exposure, and Substrate Orientation on Microbial Bioerosion in the Ionian Sea (Eastern Mediterranean)

Abstract: The effects of water depth, seasonal exposure, and substrate orientation on microbioerosion were studied by means of a settlement experiment deployed in 15, 50, 100, and 250 m water depth south-west of the Peloponnese Peninsula (Greece). At each depth, an experimental platform was exposed for a summer period, a winter period, and about an entire year. On the up- and down-facing side of each platform, substrates were fixed to document the succession of bioerosion traces, and to measure variations in bioerosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Measured depths of penetration in all substrates at the CO 2 venting areas in Ischia and Faial were particularly low (<30 μm after 6 months at Faial) and always lower than those found at ambient pH. Those depths, due mainly to Phaeophila sp., were similar to those reported by several authors for various carbonate substrates in warm temperate (Färber et al, 2015) and shallow tropical settings (Carreiro-Silva et al, 2009Enochs et al, 2016;Kiene et al, 1995;Mao Che et al, 1996). Phaeophila sp.…”
Section: Microboring Communities Under Naturally Acidified Waterssupporting
confidence: 91%
“…Measured depths of penetration in all substrates at the CO 2 venting areas in Ischia and Faial were particularly low (<30 μm after 6 months at Faial) and always lower than those found at ambient pH. Those depths, due mainly to Phaeophila sp., were similar to those reported by several authors for various carbonate substrates in warm temperate (Färber et al, 2015) and shallow tropical settings (Carreiro-Silva et al, 2009Enochs et al, 2016;Kiene et al, 1995;Mao Che et al, 1996). Phaeophila sp.…”
Section: Microboring Communities Under Naturally Acidified Waterssupporting
confidence: 91%
“…Gloeocapsa polydermatica Kützing found in Nigrita hot springs (Anagnostidis 1961) is currently regarded as a taxonomic synonym of the chlorophyte Sporotetras polydermatica (Kützing) I.Kostikov, T.Darienko, A.Lukesová, & L.Hoffmann (Guiry and Guiry 2016). The taxon Scolecia filosa found in microbial bioerosion at an underwater marine site in Peloponnese (Färber et al 2015) belongs to ichnotaxa produced by unknown heterotrophic organisms (Heindel et al 2009), not cyanobacteria. The remaining 17 species belong to the family Pelonemataceae; this family, consisting of the genera Achroonema , Pelonema , Peloploca , and Desmanthos , was created to accommodate some colorless bacteria with multicellular filaments (trichomes), which were observed in hypolimnia of lakes and ponds or in sulfur springs (Hirsch 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Orthogonum-form 1 was until now also only described from the Kosterfjord and is therefore also restricted to cold-temperate and polar regions (Wisshak 2006). Saccomorpha clava is usually a ubiquitous fungal ichnotaxon (e.g., Wisshak 2006;Wisshak et al 2011;Färber et al 2015), but only one single colony was observed in Mosselbukta, whilst we commonly found S. guttulata as a substitute of this trace. Fascichnus isp.…”
Section: Comparison With Lower Latitudesmentioning
confidence: 63%